2022
DOI: 10.18699/vjgb-22-34
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of potato spindle tuber viroid between <i>Phytophthora infestans</i> and host plants

Abstract: Potato spindle tuber viroid (PSTVd) is a naked, circular, single-stranded RNA (356–363 nucleotides in length) which lacks any protein-coding sequences. It is an economically important pathogen and is classified as a high-risk plant quarantine disease. Moreover, it is known that PSTVd is mechanically transmitted by vegetative plant propagation through infected pollen, and by aphids. The aim of this study is to determine the possibility of viroid transmission by potato pathogen Phytophthora infestans (Mont.) de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…We further demonstrated that HSVd could be bi-directionally transmitted between plant and fungus during the fungal colonization of the plant. Similarly, the transmission of PSTVd between P. infestans and the host plants under laboratory conditions was also recently demonstrated [ 16 ]. However, the occurrence of the cross-kingdom infection of viroids between plants and fungi in natural settings is still unexplored.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…We further demonstrated that HSVd could be bi-directionally transmitted between plant and fungus during the fungal colonization of the plant. Similarly, the transmission of PSTVd between P. infestans and the host plants under laboratory conditions was also recently demonstrated [ 16 ]. However, the occurrence of the cross-kingdom infection of viroids between plants and fungi in natural settings is still unexplored.…”
Section: Introductionmentioning
confidence: 82%
“…Viroids have been reported to infect and replicate in susceptible plant species [ 2 , 11 , 12 ], the unicellular yeast fungus Saccharomyces cerevisiae [ 13 ], cyanobacteria [ 14 ], filamentous plant-pathogenic fungi [ 15 ], and to some extent, an oomycete Phytoptora infestant [ 16 ]. Previously, our research group artificially introduced viroids into three filamentous plant pathogenic ascomycete fungi, Cryphonectria parasitica , Valsa mali , and Fusarium graminearum via the transfection of fungal spheroplasts with viroid RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, artificial inoculations showed that fungi are suitable hosts of plant viruses of the phylum Kitrinoviricota , such as in the case of the replication of brome mosaic virus (genus Bromovirus , family Bromoviridae ) and tomato bushy stunt virus (genus Tombusvirus , family Tombusviridae ) in Saccharomyces cerevisiae (yeast), a unicellular fungus [ 15 , 16 ], and the replication of tobacco mosaic virus (TMV, genus Tobamovirus , family Virgaviridae ) and other plant RNA viruses in plant pathogenic filamentous ascomycetes fungi, Colletotrichum acutatum, and Fusarium graminearum as well as in the plant pathogenic oomycete Phytophthora infestans [ 17 , 18 , 19 ]. Moreover, by artificial inoculation, some viroids, subviral agents of plants, were shown to infect plant pathogenic ascomycetes, Cryphonectria parasitica , Valsa mali, and F. graminearum, as well as P. infestans [ 20 , 21 ]. Importantly, our research group discovered the natural infection of a plant virus in a plant pathogenic basidiomycetous fungus.…”
Section: Introductionmentioning
confidence: 99%
“…Under laboratory conditions, CMV, TMV, viroid, and the fungal virus Cryphonectria hypovirus 1 (genus Hypovirus , family Hypoviridae ) can be bidirectionally transferred between the plant and fungus or oomycete during the fungal colonialization of plants [ 19 , 20 , 21 , 22 ]. This observation is in line with the current knowledge that during fungal infection, plants and fungi interact by exchanging cellular contents, including various macromolecules such as protein effectors and small RNAs [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…TMV was also shown to replicate in F. graminearum by inoculation through the transfection of fungal protoplasts [ 63 ]. Moreover, C. parasitica , Valsa mali , F. graminearum , and the oomycete Phytoptora infestans can also host plant viroids, the subviral agents [ 64 , 65 ]. Importantly, our study previously discovered a natural infection of cucumber mosaic virus (CMV, genus Cucumovirus ) in Rhizoctonia solani strains isolated from a potato plant [ 66 ].…”
Section: Introductionmentioning
confidence: 99%